BIOLOGICAL ACTIVITY OF PHENOLIC COMPOUNDS RELEASED FROM BARLEY AND SAFFLOWER WITHIN THREE GROWTH STAGES (SEEDLINGS, ELONGATION, AND FLOWERING) ON BARLEY AND SAFFLOWER CROPS GROWTH - ِAlaa Ibraheem; Wasan Hussain; Salim Antar (Mesopotamia Journal of Agriculture)
Experiments were designed according to Randomized Complete Block Design (RCBD)to study the effect of barley and safflower leachate at three growth stages (seedlings, elongation, and flowering) on seed germination and growth of barley and safflower varieties. The study included conducting two experiments in the greenhouse of the Biology Department/ Science College/ Mosul University, on 20/10/2023. The results showed a variation in effect between increases and decreases depending on treatments, stages of growth, and traits studied. Several phenolic compounds were identified using HPLC techniques in the safflower plant (Ferulic acid, gallic acid, kaempferol, Rutin), while ferulic acid (gallic acid, apigenin, luteolin) was identified in barley plants. The results indicated differences in concentration of chemical compounds isolated from plant residues of barley and safflower for growth stages (seedlings, elongation, flowering). It was found that the highest concentration of Gallic acid compound was for barley and safflower in all stages of growth identified compounds gave the highest Concentrations in seedling stage of both plants, while flowering stage recorded lowest concentrations.